Driving the Circular Economy Through Digital Servitization: Sustainable Business Models in the Maritime Sector - Viktoriia Koilo (Businesses)
This study explores the integration of digitalization and circular economy (CE) principles within the maritime industry through a theoretical analysis, proposing a framework that aligns business models with Sustainable Development Goals (SDGs) and net-zero objectives. By investigating how digital servitization and circular business models can drive economic, social, and environmental outcomes, this research provides valuable insights into sustainable value creation and capture across maritime value chains. The theoretical analysis covers the evolution of business models, emphasizing their collective role in fostering sustainable transformation within the maritime sector. The central idea of this study is a sustainable value mapping approach that aligns product–service systems (PSSs) with circular economy principles, incorporating lifecycle thinking (LCT) to capture the full environmental, economic, and social impacts. This broader perspective on the economic value proposition highlights the need for a shift from selling products to offering servitized products, acknowledging the importance of sustainability across the entire product lifecycle. This framework offers actionable guidance for maritime stakeholders committed to transitioning their value chains towards sustainable, circular models, addressing both production and consumption dimensions to achieve broader environmental and social benefits.